2020
DOI: 10.1002/ca.23667
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical study of the soleus: Application to improved imaging diagnoses

Abstract: Introduction Strains of the soleus are widely found both in amateur and professional athletes. For their accurate regional diagnoses, understanding the anatomy of the spatial relationship between muscular fibers and tendinous structures is important because their interfaces are susceptible sites to muscle strains. Therefore, this study evaluated the precise architecture of the soleus. Materials and Methods We evaluated the precise anatomical architecture of the soleus in 87 formaldehyde‐fixed soleus muscles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent studies on the skeletal muscles by the present authors have shown the usefulness of isolated muscle specimens to analyze the arrangement of muscle fascicles in the muscle body to provide essentially important information for the mechanical function of the muscles [11,16,22]. The facial muscles have scarcely been studied utilizing isolated muscle specimens, except in old anatomical atlases [3,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the skeletal muscles by the present authors have shown the usefulness of isolated muscle specimens to analyze the arrangement of muscle fascicles in the muscle body to provide essentially important information for the mechanical function of the muscles [11,16,22]. The facial muscles have scarcely been studied utilizing isolated muscle specimens, except in old anatomical atlases [3,19].…”
Section: Introductionmentioning
confidence: 99%